O marco jurídico da economia solidária no Brasil: entre a geração de trabalho e renda e a desoneração do capital. - Luciano Ricardo de Magalhaes Pereira (2008)
The present thesis aims at analyzing, in the field of work relations in Brazil, the way the proposals of constitution of a new judicial limit of the solidary economy, presented by the organized movement in the Brazilian Forum of Solidary Economy (FBES) and by the National Office of the Solidary Economy (SENAES), organ linked to the Ministry of Labor and Employment (MTE), promote the conversion of the salaried work to the associated work throughout the labor cooperatives. It also demonstrates, from a documental and literary research, that this enterprise to promote the judicial regulation of the solidary economy may contribute for the deepening process of deregulation and flexibilization of the work relations. The debates and actions taken as reference for this analysis refer to the period of the governments of the presidents Fernando Henrique Cardoso and Luiz Inácio Lula da Silva.